Interest Rate Sensitivity, Market Risk, Inflation and Bank Stock Returns - Mohammad I. Al-Abadi; Orouba W. Al- Sabbagh (Journal of Accounting, Business and Management (JABM), 2006)
This study provides empirical evidence on the risk-return trade-off interaction by testing for interest rate risk, market risk and inflation, on one hand, and stock returns, on the other hand. To do so, three models are applied, each of which is focusing on measuring a specific type of risk and the impact made on banks stock return. The study applied the CAPM in which the single index model is used to test for the impact of market risk, as well as the two-factor model which is used to incorporate the effect of interest rate risk. The two-factor model is extended to multi-factor model to test for an additional macroeconomic factor typified by both tails of expected and unexpected inflation. The study is comprised of a sample based on the most representative thirteen Jordanian commercial and investment banks. The sample interval spans over a period that encompasses thirteen annual financial years, 1990-2003, inclusive, all are in monthly basis. The result indicates that market risk has a positive and significant association with stock returns, while the interest rate factor has a significant and negative impact on stock returns. In reference to the inflation risk factor, the result shows that expected inflation has a negative and significant impact, while unexpected inflation has a negative but insignificant impact in their relationship with the stock returns.